Differences in ejection fraction as inclusion criterion in randomized controlled trials among patients with heart failure with reduced ejection fraction: a systematic review. (3rd June 2022) - Al Sudani, Hussein; Lo, Kevin Bryan; Essa, Hani; Wattoo, Ammaar; Gulab, Asma; Akhtar, Hamza; Angelim, Lucas; Helfman, Beth; Peterson, Eric; Brousas, Sophia; Whybrow-Huppatz, Isabel; Yazdanyar, Ali; et al.
ABSTRACT: Introduction: Heart failure (HF) with reduced ejection fraction (HFrEF) has been defined by varying ejection fraction (EF) criteria in clinical trials, leading to differences in quantifying treatment effects. Areas covered: The definitions of HFrEF in randomized controlled trials from 2010 until 2020 were collected. The EF ranges were clustered into very low (<30%), low (30–39%) and mildly reduced (40–49%) stratified by intervention. A time series regression analysis was performed. A total of 3052 articles were screened and 706 were included. Interventions included were pharmacologic (37%), device therapy (10%), and a combination of programs, procedural, and laboratory testing (53%). Regarding EF cutoffs, 41% of the studies utilized <40% while 26% used <35%. About 31% did not have a clearly defined EF. Between 2010 and 2020, studies with HFrEF ranges 30–39% have significantly decreased (p value < 0.001 for trend), but those which included very low EF (<30%) and mildly reduced EF (40–49%) have remained the same. Expert opinion: EF definitions across clinical trials in HFrEF varied widely. Defining the specific target HF population phenotype when designing trials or in patient treatment is important as various beneficial effects of different heart failure treatment modalities can be modified or even attenuated across the spectrum of EF.